Ability and disability in autism spectrum disorder: a systematic literature review employing the international classification of functioning,disability and health-children and youth version - Schipper, Elles de; Bölte, Sven (Autism research, 2015)
Objective: This study is the first in a series of four empirical investigations to develop International Classification of Functioning, Disability and Health (ICF) Core Sets for Autism Spectrum Disorder (ASD). The objective was to use a systematic review approach to identify, number, and link functional ability and disability concepts used in the scientific ASD literature to the nomenclature of the ICF-CY (Children and Youth version of the ICF, covering the life span). Methods: Systematic searches on outcome studies of ASD were carried out in Medline/PubMed, PsycINFO, ERIC and Cinahl, and relevant functional ability and disability concepts extracted from the included studies. These concepts were then linked to the ICF-CY by two independent researchers using a standardized linking procedure. New concepts were extracted from the studies until saturation of identified ICF-CY categories was reached. Results: Seventy-one studies were included in the final analysis and 2475 meaningful concepts contained in these studies were linked to 146 ICF-CY categories. Of these, 99 categories were considered most relevant to ASD (i.e., identified in at least 5% of the studies), of which 63 were related to Activities and Participation, 28 were related to Body functions, and 8 were related to Environmental factors. The five most frequently identified categories were basic interpersonal interactions (51%), emotional functions (49%), complex interpersonal interactions (48%), attention functions (44%), and mental functions of language (44%). Conclusion: The broad variety of ICF-CY categories identified in this study reflects the heterogeneity of functional differences found in ASD—both with respect to disability and exceptionality—and underlines the potential value of the ICF-CY as a framework to capture an individual's functioning in all dimensions of life. The current results in combination with three additional preparatory studies (expert survey, focus groups, and clinical study) will provide the scientific basis for defining the ICF Core Sets for ASD for multipurpose use in basic and applied research and every day clinical practice of ASD. Autism Res 2015, 8: 782-794. © 2015 The Authors Autism Research published by Wiley Periodicals, Inc. on behalf of International Society for Autism Research
Gesehen am 29.11.2018